Pokémon go: un videojuego activo que puede incrementar las habilidades sociales en jóvenes de Lima Metropolitana - Quiñones Hague, Valeria Maria (2022)
The deficit of social skills during emerging adulthood can generate as main consequences the emergence of emotional disorders and risk behaviors. As a result of this, the importance of knowing new complementary alternatives of interest for said population arises, being a good option the use of videogames, with the purpose of increasing these skills. This descriptive comparative study focused on contrasting two groups of young people between 18 and 22 years of age living in Metropolitan Lima in order to observe if the group that used an active video game known as Pokémon Go had better scores in their social skills. Goldstein's Social Skills Checklist (1989) was applied to both groups and the data obtained were analyzed using the Mann Whitney test. The results showed that the group of gamers obtained significantly higher scores in their social skills than the second group. In addition, a predominance of scores by female players was observed. Finally, the experience time, the consumption of hours and the use of weekly days did not influence the scores achieved by the participating players.